THE IMPACT OF PHYSICAL ACTIVITY ON AUTOIMMUNE DISEASES: A NARRATIVE REVIEW OF MECHANISMS, OUTCOMES AND PRACTICAL IMPLICATIONS - Karolina Błądzińska,; Maciej Błądziński,; Małgorzata Zach,; Kacper Szeląg,; Barbara Wołoszyn, (International Journal of Innovative Technologies in Social Science, 2025)
Autoimmune diseases are chronic, heterogeneous disorders characterized by immune-mediated tissue damage, systemic inflammation, and reduced quality of life. Pharmacological treatments often alleviate symptoms but rarely address functional limitations such as fatigue, deconditioning, and psychosocial distress. Physical activity (PA) is increasingly recognized as a safe and effective adjunctive therapy. This narrative review synthesizes biological mechanisms, disease-specific outcomes, and practical applications of PA across major autoimmune conditions including rheumatoid arthritis (RA), multiple sclerosis (MS), systemic lupus erythematosus (SLE), inflammatory bowel disease (IBD), and type 1 diabetes (T1D). Evidence shows that PA functions as a multimodal immunomodulator, reducing pro-inflammatory cytokines, enhancing regulatory T-cell activity, rebalancing adipokines, recalibrating neuroendocrine pathways, and supporting microbiome diversity. Clinically, PA improves fatigue, functional capacity, mood, and cardiometabolic risk, without increasing relapse or flare frequency. The FITT framework (Frequency, Intensity, Time, Type) offers a practical model for prescribing exercise, with disease-specific adaptations ensuring safety and adherence. Despite strong evidence, implementation remains limited due to patient fears, clinician knowledge gaps, and systemic barriers. Digital health and tele-exercise hold promise for precision exercise medicine. In conclusion, physical activity is a safe, effective, and indispensable adjunct in autoimmune disease management, warranting integration into standard care pathways.